Farmers' adaptive capacity towards the impacts of global warming: a review - Hamdan, Mas Ernawati; Man, Norsida; Md. Yassin, Sulaiman; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril (Canadian Center of Science and Education, 2013)
Global warming has been detected in Malaysia, and is predicted to worsen in the future. Agriculture is highly dependent on weather stability, and warmer climates are expected to cause formidable challenges to industry. This paper focuses on the impacts of rising temperatures on the environment and farmers’ socio-economic situations. Data were obtained through a literature review and document analyses. It can be concluded that rising temperatures have had direct effects on agricultural products, which then affects the income and productivity of farmers. Furthermore, rising temperatures have been found to affect farmers’ health and obstruct their social routines, while causing a shortage in terms of food supply. A brief discussion on the need for adaptation is also highlighted, and hopefully this will assist concerned parties to develop adaptation strategies that are in line with farmers’ needs and abilities.